KINEMATIC GAIT ANALYSIS IN HEMIPLEGIC PATIENTS - Şenay Özdolap,; Aynur Karagöz,; Ayşe Karamercan,; Neşe Özgirgin, (Archives of Rheumatology, 2001)
In this study, kinematic gait analysis was performed in 46 (22 male, 24 female) hemiplegic patients. We investigated the effects of clinical characteristics, lower extremity motor status, functional ambulation category, type of ambulation aid and orthosis on temporal-distance (TD) variables. The age of patients, sex, hemiplegic side, aetiology and disease duration were not related to these parameters but lower extremity motor status, functional ambulation category, type of ambulation aid and orthosis were related significantly to TD variables.